Field-Oriented Control of Multiphase Drives with Passive Fault Tolerance - González Prieto, Ignacio; Durán-Martínez, Mario Javier; García Entrambasaguas, Paula; Bermúdez, Mario (IEEE, 2020)
Multiphase machines provide a continuous operation of the drive with no additional hardware in the event of one or more open-phase faults. This fault-tolerant capability is highly appreciated by industry for security and economic reasons. However, the steady-state postfault operation has only been feasible in previous works after the fault localization and control reconfiguration. Even though this is done at the software stage, the obligation to identify the faulty phases and store the modifications for every fault scenario adds further complexity. This article reveals that this software reconfiguration can be avoided if the field-oriented control strategy is designed to satisfactorily handle pre and postfault situations. Experimental results confirm the capability to obtain a suitable postfault operation without fault localization and control reconfiguration and, thus, achieving a passive/natural fault tolerance.
Keywords: Máquinas eléctricas; Multiphase drives; Induction motors; Field-oriented control (FOC); Fault tolerance